2020
DOI: 10.3389/fpsyg.2020.551824
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions and Morphosyntax: Distinguishing DLD From ADHD in French-Speaking Children

Abstract: Attention deficit hyperactivity disorder (ADHD) is commonly associated with deficits in executive functions executive functions (EF), but children with this disorder frequently demonstrate co-occurring morphosyntactic impairment when assessed using standardized tests. On the other hand, children with developmental language disorder (DLD), a population defined by impaired linguistic functioning, are often diagnosed with comorbid EF deficits. We investigated EF and morphosyntax in 60 Frenchspeaking children aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 69 publications
(114 reference statements)
4
16
0
1
Order By: Relevance
“…Future studies should also evaluate these transfer effects in children with DLD. Similar effects would be expected, consistent with studies linking attentional resources to the processing of complex syntax in children with DLD (Montgomery et al, 2009 ; Stanford & Delage, 2020 ). Moreover, it would be informative to contrast effects of pure training of the attentional component (such as the TALI, Kirk et al, 2016 ) with effects in the current study, and to compare effects of both on syntax; this would reveal whether linguistic gains following intensive WM training can be attributed to WM improvements or to better functioning of the attentional system.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Future studies should also evaluate these transfer effects in children with DLD. Similar effects would be expected, consistent with studies linking attentional resources to the processing of complex syntax in children with DLD (Montgomery et al, 2009 ; Stanford & Delage, 2020 ). Moreover, it would be informative to contrast effects of pure training of the attentional component (such as the TALI, Kirk et al, 2016 ) with effects in the current study, and to compare effects of both on syntax; this would reveal whether linguistic gains following intensive WM training can be attributed to WM improvements or to better functioning of the attentional system.…”
Section: Discussionsupporting
confidence: 86%
“…Executive functions are linked to syntactic capacities, in typically-developing children (e.g., Finney et al, 2014 ; Ibbotson & Kearvell-White, 2015 ; Viterbori et al, 2012 ; White et al, 2017 ), in children who present either syntactic difficulties, such as children with DLD (Ellis Weismer & Thordardottir, 2002 ; Im-Bolter et al, 2006 ; Montgomery, 2008 ; Montgomery et al, 2009 ), and in executive dysfunction such as ADHD (Stanford & Delage, 2020 ).…”
Section: Working Memory and Syntaxmentioning
confidence: 99%
“…Analysis of individual results also highlighted that poor performance on the standardized syntax assessment that was part of our pre-test evaluation was not always associated with difficulty producing the passive in the priming task. For children with ADHD, this is in line with recent work done by Stanford and Delage (2020) showing that this population is more likely to perform poorly on omnibus syntax tests that contain a variety of syntactic structures than on probe syntax tests that focus on one specific construction. In the case of children with DLD, the fact that more than half of these participants were able to reach ceiling or near ceiling levels of accuracy for passive production following the final linguistic cue offers strong support for the added value of including Dynamic Assessment paradigms (Hasson et al, 2013;Hasson & Joffe, 2007), which focus on the extent to which an individual's language performance is modifiable, when evaluating children's syntactic abilities, a method that has become increasingly popular among speech-language practitioners.…”
Section: Additional Analysessupporting
confidence: 88%
“…Using more finegrained measures to assess seven-to-eight-year-old children with ADHD on (i) the repetition of active and passive sentences containing ten to 14 syllables and (ii) the production of past tense morphology, which are both clinical markers of DLD in English, Redmond et al (2011) showed that children with ADHD performed comparably to typically developing (TD) children on the two syntax tasks and that both ADHD and TD performance was significantly better than that of children with DLD. Similar results were found in schoolaged French-speaking children: children with ADHD could be distinguished from children with DLD when tested on the production of third person object pronouns, a reliable clinical marker of DLD in French (Stanford & Delage, 2020). In the same study, children with ADHD showed performance approaching that of children with DLD when tested on a variety of structures using a standardized evaluation that is commonly employed to identify DLD in French-speaking children, pointing to a clear asymmetry between ADHD performance on omnibus syntactic evaluations and those that are more targeted.…”
Section: Syntax In Dld and Adhdsupporting
confidence: 78%
“…Il apparaît que les mesures de bien-être émotionnel ne corrèlent pas avec les mesures de langage. En revanche, la mémoire de travail verbale et les capacités d'inhibition corrèlent avec les résultats obtenus aux différentes tâches Litmus, répliquant de précédentes observations sur les liens existants entre fonctions exécutives et langage (Delage & Frauenfelder, 2020 ;Stanford & Delage, 2020 ;Stanford, 2020 ;Viterbori et al, 2012).…”
Section: Méthode Généraleunclassified